EFFECTIVENESS OF PHYSICAL THERAPY IN RESTORING LOWER LIMB FUNCTIONS IN MILITARY SERVICEMEN AFTER MINE AND EXPLOSIVE INJURIES (Physical Culture and Sport: Scientific Perspective, 2025)
Rehabilitation of military personnel who have suffered as a result of armed conflicts or traumatic events is an important and pressing task of the healthcare system. In the context of the ongoing hostilities in Ukraine, the number of wounded military personnel and civilians requiring comprehensive assistance from a multidisciplinary team is increasing daily. Purpose of the study: To develop a program aimed at improving the functional state of the lower limbs in military personnel after mine-explosive injuries and to experimentally evaluate its effectiveness. Methods. The study employed theoretical research methods such as analysis, comparison, induction, deduction, systematization, and generalization of scientific and methodological literature, as well as empirical methods and statistical analysis. Results. Physical therapy is an integral component of the rehabilitation process following mine-explosive injuries, as it contributes not only to the reduction of pain and inflammation but also to the restoration of functional capacity in service members. The volume, structure, and content of physical therapy interventions included in individual rehabilitation plans for military personnel with the consequences of mine-explosive trauma should be determined based on the clinical picture, stage of the pathological process, and the nature of the injury. In the experimental group, pain intensity assessed using the Visual Analogue Scale decreased from 5.16 ± 1.17 points to 2.44 ± 1.14 points (p < 0.05), indicating significant pain relief. In the control group, pain also decreased (from 5.24 ± 1.23 to 4.22 ± 1.29; p > 0.05), but less markedly, which may reflect the lower efficacy of standard therapy in reducing pain. Conclusions. Restoration of lower limb function in military personnel after mine-explosive injuries is a complex and prolonged process that requires a comprehensive approach, in which physical therapy plays a pivotal role. Properly selected physical therapy methods contribute not only to the recovery of limb function but also to the alleviation of psychological distress, promoting full reintegration into active life and military service.
Keywords: injuries; physical therapy; functional state; military personnel